A community-based study on reproductive empowerment of women aged 15-49 years and associated factors in a rural area of Delhi - Vignitha, B.; Smanla, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Reproductive health disparities persist globally, with a significant proportion of women lacking access to modern contraception despite desiring to control their fertility, leading to a substantial number of unintended pregnancies. This study aimed to assess the level of reproductive empowerment among married women in rural areas, specifically focusing on communication, decision-making, social support, and norms related to reproductive health. Methods: A cross-sectional study was conducted in the rural areas of south Delhi, with a sample size of 215 married women aged 15-49 years. Systematic random sampling was employed, and data was collected using a semi-structured questionnaire validated in Hindi. The reproductive empowerment (RE) scale was utilized, comprising sub-scales related to healthcare provider communication, partner communication, decision-making, social support, and social norms. Data analysis was performed using SPSS software, with a significance level set at p<0.05. Results: The study reveals that 54.8% of the participants exhibited high levels of reproductive empowerment. The mean RE score was 3.09±0.39 out of 4, indicating moderate to high levels of empowerment. Sub-scale analysis showed higher scores in healthcare provider communication (3.91±0.28) compared to decision-making (2.93±0.65), partner communication (3.53±0.69), social support (2.19±0.89), and social norms (2.13±0.69). Conclusions: This study underscores the importance of exploring reproductive empowerment as a specific entity and advocates for further research and interventions to promote women’s agency and decision-making autonomy in matters of reproductive health.